Damping effect on supersonic panel flutter of composite plate with viscoelastic mid-layer. (March 2016) - Yang, Xiao-Dong; Yu, Tian-Jun; Zhang, Wei; Qian, Ying-Jing; Yao, Ming-Hui
Abstract: The panel flutter of composite plate with viscoelastic mid-layer in supersonic airflow is investigated in this study. The hysteric damping model is used to describe the viscoelastic property of the mid-layer material and the first piston theory to model the aerodynamic forces. Hamilton's principle is employed to derive the partial differential equations governing the vibrations of the laminated composite plate. By Galerkin method the governing partial differential equations are truncated into a set of ordinary differential equations. The critical dynamic pressure for panel flutter has been studied by considering the eigenvalue problem of the set of ODEs. It was concluded that the introduction of aerodynamic damping postpones the threshold of flutter, while the viscoelastic damping of the soft mid-layer presents a phenomenon of dual effect. When the viscoelastic damping value is low, the internal material damping shows detrimental effect to the flutter depression. If the viscoelastic damping is increased further, the flutter resistance of the composite plate will be enhanced. The convergence of the Galerkin method is also discussed in this study. The influences of some parameters to the convergence have been investigated in details.